Instrument to evaluate the behavioral intention of hypertensive people when taking anti-hypertensives - Taciana da Costa Farias Almeida; Mailson Marques de Sousa; Bernadete de Lourdes André Gouveia; Ricardo Alves de Olinda; Maria Eliane Moreira Freire; Simone Helena dos Santos Oliveira
ABSTRACT Objectives: to build and analyze the validity of an instrument to assess the behavioral intention of individuals with hypertension to take antihypertensive pills. Methods: methodological study based on the theory of planned behavior, developed in three stages: preparation of the instrument, validation of content and pre-test with the target audience. The content has been validated by six experts. The Content Validity Index was applied. Results: five nurses and one psychologist participated, with experiences in systemic arterial hypertension and/or planned behavior theory. The first version of the instrument contained 40 items. After analysis, the second version originated, with 36 items. 100% agreement was obtained for the scope of the constructions. The pre-test showed clarity and understanding of the items by the target audience. Conclusions: the instrument is a reliable and innovative technological product for use in populations with systemic arterial hypertension and beliefs similar to those identified in the surveyed group.